Case Report: Kidney Transplantation in a Patient With Acquired Agammaglobulinemia and SLE. Issues and Challenges - Pavlakou, Paraskevi; Papasotiriou, Marios; Ntrinias, Theodoros; Kourakli, Alexandra; Bratsiakou, Adamantia; Goumenos, Dimitrios S.; Papachristou, Evangelos (Frontiers in Medicine, 2021)
Lupus nephritis in the context of Systemic Lupus Erythematosus (SLE) is characterized by an unpredicted course with remissions and flare-ups. Among others, it remains a significant cause of end-stage kidney disease (ESKD) in relatively young patients. Therapeutic regimens with newer immunosuppressive agents have been introduced in order to control SLE clinical manifestations more efficiently and limit organ damage induced by immune complex formation and sustained inflammation. Treatment is usually long-term, and the cumulative impact of immunosuppression is expressed through the increased frequency of infections and neoplasms. However, if the observed immunity dysregulation is secondary and pharmaceutically induced or there is a pre-existing, primary immunodeficiency that shares common pathogenetic pathways with SLE's autoimmunity is not always clear. Herein, we present the case of a 39-year-old woman, that reached ESKD due to lupus nephritis. After an upper respiratory cytomegalovirus (CMV) infection and concomitant CMV reactivations the investigation revealed significant immunodeficiency. Not long after the initiation of intravenous immunoglobulin (IVIG) administration, patient received a cadaveric kidney transplant. IVIG was continued along with standard immunosuppression so that both recurrent infections and allograft rejection are avoided. Patient is closely monitored, and her post-transplant course is remarkably satisfying so far. ESKD patients with immunodeficiency syndromes should not be excluded by definition from kidney transplantation.